INDIGENOUS LITIGANTS AND LEGAL PROCESSES IN BOLIVIA: : Ten years after the plurinational route - Paz, Sarela (Universidade de Brasília, 2021)
This study seeks to understand how the paths of interlegality are developing in Bolivia from dynamics that are inscribed in litigation undertaken by indigenous peasants, in a context of egalitarian legal pluralism that is activated as a constitutional principle.